A UV to X-Ray View of Soft Excess in Type 1 Active Galactic Nuclei. I. Sample Selection and Spectral Profile - Shi-Jiang Chen; Jun-Xian Wang; Jia-Lai Kang; Wen-Yong Kang; Hao Sou; Teng Liu; Zhen-Yi Cai; Zhen-Bo Su (The Astrophysical Journal)
A core sample of 59 unobscured type 1 active galactic nuclei (AGNs) with simultaneous XMM-Newton X-ray and UV observations is compiled from the archives to probe the nature of soft X-ray excess (SE). In the first paper of this series, our focus centers on scrutinizing the spectral profile of the soft excess. Of the sources, ≈71% (42/59) exhibit power-law-like (po-like) soft excess, while ≈29% (17/59) exhibit blackbody-like (bb-like) soft excess. We show that a cutoff power law could uniformly characterize both types of soft excesses, with a median E _cut of 1.40 keV for po-like and 0.14 keV for bb-like. For the first time, we report a robust and quantitative correlation between the SE profile and SE strength (the ratio of SE luminosity to that of the primary power-law continuum in 0.5–2.0 keV), indicating that stronger soft excess is more likely to be po-like, or effectively has a higher E _cut . This correlation cannot be explained by ionized disk reflection alone, which produces mostly bb-like soft excess ( E _cut ~ 0.1 keV) as revealed by relxilllp simulation. Remarkably, we show with simulations that a toy hybrid scenario, where both ionized disk reflection ( relxilllp , with all reflection parameters fixed at default values except for ionization of the disk) and warm corona ( compTT , with temperature fixed at 1 keV) contribute to the observed soft excess, can successfully reproduce the observed correlation. This highlights the ubiquitous hybrid nature of the SE in AGNs, and underscores the importance of considering both components while fitting the spectra of soft excess.